The Effect of Counseling with Lecture and Leaflet Methods on Knowledge and Attitudes of Pregnant Women in Providing Basic Immunization - Eka Purnamasari; Namora Lumongga Lubis; Taufik Ashar (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2020)
Complete basic immunization coverage in Labuhan District is still low at 71.15%. Therefore, counseling is needed to change the behavior of parents in complete basic immunization to toddlers. The aim of this study was to determine the effect of counseling using the lecture method and the lecture method accompanied by leaflets on changes in maternal behavior in providing complete basic immunization at the Santosa Bay Health Center in Labuhanbatu Regency. This type of research is Quasi Experiment Design, with the design of Non-Equivalent Control Group. The intervention group consisted of two research subjects who were given different treatments and one research subject was made into the control group. This research was carried out in the work area of the Santosa Bay Health Center in LabuhanBatu Regency. The population in the study were all Trisemester III Pregnant Women as many as 188 people and the sample in this study were 75 people. Data analysis used included T-dependent, Wilcoxon, and Kruskal Walis. The results showed that there were differences (p= <0.001) and attitudes (p= <0.001) about basic immunization with the lecture method. There are differences in knowledge (p= <0.001) and attitudes (p= <0.001) with the lecture method accompanied by leaflets. There is a significant difference between the increase in knowledge and attitudes that get treatment counseling using the lecture method and the lecture method accompanied by leaflets. Changes in knowledge and the highest attitude on the group given the lecture accompanied by leafleat. For Teluk Sentosa Health Center, Labuhanbatu Regency, it should make a program with a routine schedule in the implementation of counseling for pregnant women both on basic immunization or related to the health and safety of mothers and babies. Where is the lecture method either without using media or by using alternative methods in implementing the program.